Perioperative outcomes of women with advanced ovarian cancer: A comparison of two historic cohorts at Tygerberg Academic Hospital - Phakathi, Nomkhosi Lungile (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed) -- Stellenbosch University, 2024.